2005
DOI: 10.1128/aem.71.11.7567-7570.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Bacteriocin Resistance and Inactivation of Listeria innocua LMG 13568 by Lactobacillus sakei CTC 494 under Sausage Fermentation Conditions

Abstract: In mixed cultures, bacteriocin production by the sausage isolate Lactobacillus sakei CTC 494 rapidly inactivated sensitive Listeria innocua LMG 13568 cells, even at low bacteriocin activity levels. A small fraction of the listerial population was bacteriocin resistant. However, sausage fermentation conditions inhibited regrowth of resistant cells.Lactobacillus sakei CTC 494, producer of the bacteriocin sakacin K, inhibits Listeria spp. during sausage fermentation (12). Bacteriocins are small peptides or protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In particular, such information is essential when dealing with the potential problem of bacteriocin-resistant target bacteria [44,45] . Application of bacteriocin-producing starter cultures in sourdough (to increase competitiveness and hence establish a desired microbial population), in fermented sausage (anti-listerial effect to meet the zero-tolerance policy in ready-toeat foods), and in cheese (anti-listerial and anti-clostridial effects), have been studied during in vitro laboratory fermentations as well as on pilot-scale level [19,41,[44][45][46][47][48][49] . Results of these studies were highly promising and underline the important role that functional, bacteriocinogenic strains of LAB may play in the food industry as starter cultures, co-cultures, or bioprotective cultures, to improve food quality and safety [2,3,13] .…”
Section: Bacteriocin Production In Foods: Application Possibilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, such information is essential when dealing with the potential problem of bacteriocin-resistant target bacteria [44,45] . Application of bacteriocin-producing starter cultures in sourdough (to increase competitiveness and hence establish a desired microbial population), in fermented sausage (anti-listerial effect to meet the zero-tolerance policy in ready-toeat foods), and in cheese (anti-listerial and anti-clostridial effects), have been studied during in vitro laboratory fermentations as well as on pilot-scale level [19,41,[44][45][46][47][48][49] . Results of these studies were highly promising and underline the important role that functional, bacteriocinogenic strains of LAB may play in the food industry as starter cultures, co-cultures, or bioprotective cultures, to improve food quality and safety [2,3,13] .…”
Section: Bacteriocin Production In Foods: Application Possibilitiesmentioning
confidence: 99%
“…In this way, the kinetics of bacteriocin production by LAB strains in foods have been described in detail, amongst others through mathematical modeling and positive predictive microbiology [43] . Insights in the relationship between the food environment and kinetics of the starter culture have yielded valuable information about the in situ production of bacteriocins and its interactions with the target strains, which will be important if bacteriocins or bacteriocinproducing strains are to be increasingly used in food systems [19,44,45] . In particular, such information is essential when dealing with the potential problem of bacteriocin-resistant target bacteria [44,45] .…”
Section: Bacteriocin Production In Foods: Application Possibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these models are the vitalistic models proposed by Cole et al (13,28,39), models describing both growth and inactivation (26,27,32,37,40,41), the modified Gompertz model (24,32), the exponential model (31), and the log-linear model with latency time (6) and/or with a tail (5). These models cannot deal with all shapes of curves, and most of them are based on log-linear inactivation.…”
mentioning
confidence: 99%
“…The occurrence of stress-resistant variants in monoclonal populations of bacteria remains an important subject of debate, as some research groups have reported the isolation of such variants while others failed to demonstrate their presence and questioned their existence (1,3,5,16,17,19,24,29,31). In this study, we used a new strategy involving a kinetic modeling-based sampling scheme and an optimized stress challenge cycle method for the isolation of stress-resistant variants of L. monocytogenes.…”
Section: Discussionmentioning
confidence: 99%